EVALUATION OF THE EFFECTIVENESS RATIO FOR THE ALLOCATION OF VILLAGE FUNDS - Andriyani, Fitriya; Ardhiarisca, Oryza; Pramista Titis Wangi, Anggun (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: The purpose of this study is to evaluate how well ADD is working in Gentong Village, Taman Krocok District, Bondowoso Regency, to execute village development. Methods: The method used for this research is qualitative research with a case study approach. Analysis data: The data analysis technique uses the effectiveness ratio number. Result and discussions: The results showed that the use of ADD in Gentong Village, Taman Krocok District, was effective in increasing village development. Conclusion: ADD has been used to build bridges, roads, public toilets (MCK), and the Clean Water/Pamsimas Program. However, there are still challenges in using ADD in Gentong Village, Taman Krocok District, such as disagreements in the field and delays in center funding disbursements. Based on the results of this study, it is suggested that the village government and the community increase their participation in the process of planning and monitoring the use of ADD. In addition, efforts are also needed in more effective ADD financial management and increased coordination between the village government and other stakeholders.